Pengaruh Adaptasi Bahasa Visual Jepang pada Film Animasi Indonesia Battle of Surabaya - Cintya Dwi Hastuti; Irfansyah Irfansyah; Hafiz Aziz Ahmad (Universitas Bumigora, 2022)
The animation industry in Indonesia is currently developing positively, where its production is increasing from year to year. Various kinds of drawing styles have been widely explored and applied to Indonesian animation. Moreover, with the better quality of world animation, situationally it also encourages Indonesian animators to improvise and continue to develop creativity through their work. In the process of its development, the popularity of Japanese animation turned out to have a significant influence on the formation of Indonesian animated films. Since the first Battle of Surabaya animation appeared in the community, many speculated that this animation was adapting Japanese animation visuals. The purpose of this research is to examine more deeply the effect of Japanese Visual Language adaptation in the Indonesian animated film, Battle of Surabaya. This research is expected to be a form of scientific dedication regarding Indonesian animation, as well as an evaluation material for Indonesian animators in exploring and considering the application of animation visualization.